Composição da comunidade de diatomáceas periféricas do rio Jaú, Amazonas, Brasil - Castro, José Gerley Dias; Souza-mosimann, Roseli Maria de; Laudares-silva, Roselane; Forsberg, Bruce Rider (Acta Amazonica, 2003)
The periphytic diatom flora of the Jaú River, a tributary of the Negro River, in Amazonia (2º 57' S; 61º49' W) was studied. Algae were collected manually during the high water periods of 1995, 1996 and 1997 and permanent slides prepared from this material were deposited in the FLOR Herbarium of the Federal University of Santa Catarina. Sixty specific and infra-specific taxa were identified, distributed among 16 genuses and 13 families. Eunotiaceae was the best represented family, with 43.3% of all taxa inventoried, followed by Pinnulariaceae with 21.6% and Surirellaceae with 11.6%. Accounting for 20 taxa. Eunotia and Pinnularia were the dominant genuses and showed the broadest morphological variation. Eunotia was the best. The relevant literature for each taxon was reveiwed and discussed.", 'en
Composition of the periphytic diatom community of the Jaú river, Amazonas, Brazil
Keywords: Fresh Water Diatoms; Bacillariophyceae; Periphyton; Jau River; Amazon; Diatomáceas De Água Doce; Bacillariophyceae; Perifiton; Rio Jaú; Amazonas